The Copper Influence into Physical and Mechanical Properties of the Al-5Si Alloy - Isom Mudzakir, MSi.; Suhariyanto Suhariyanto; Renanto Putra Wijaya; Hamdan Akbar Notonegoro; Bambang Soegijono (Universitas Sultan Ageng Tirtayasa, 2021)
The microstructure and the hardness due to addition of copper of the Al-Si-Zn-Mg-Cu Alloy have been investigated. The copper has been varied from 0 wt.%– 4.9 wt.% in order to see how the microstructure and the hardness of the alloy change. The Heat treatment at temperature 510 oC during 5 hours and then cooling to ambient temperature, have done to foster the dissolution of copper in the crystal and then precipitate during cooling. The results show that the alloying element form a phase distributed in the matrix of the alloy. Increasing the content of the copper makes the form of the second phase smaller and at the matrix show fine particle distributed mostly entire of the surface. The hardness of the alloy increase as the copper content increase. The increase in hardness might come from the fine particle distributed in the matrix. The onset, endset and melting temperature tend to decrease as the copper content increase.